CD4+ T Cells Recognize Conserved Influenza A Epitopes through Shared Patterns of V-Gene Usage and Complementary Biochemical Features - Greenshields-Watson, Alexander; Attaf, Meriem; MacLachlan, Bruce J.; Whalley, Thomas; Rius, Cristina; Wall, Aaron; Lloyd, Angharad; Hughes, Hywel; Strange, Kathryn E.; Mason, Georgina H.; Schauenburg, Andrea J.; Hulin-Curtis, Sarah L.; et al. (Cell reports (Cambridge), 2020)
T cell recognition of peptides presented by human leukocyte antigens (HLAs) is mediated by the highly variable T cell receptor (TCR). Despite this built-in TCR variability, individuals can mount immune responses against viral epitopes by using identical or highly related TCRs expressed on CD8+ T cells. Characterization of these TCRs has extended our understanding of the molecular mechanisms that govern the recognition of peptide-HLA. However, few examples exist for CD4+ T cells. Here, we investigate CD4+ T cell responses to the internal proteins of the influenza A virus that correlate with protective immunity. We identify five internal epitopes that are commonly recognized by CD4+ T cells in five HLA-DR1+ subjects and show conservation across viral strains and zoonotic reservoirs. TCR repertoire analysis demonstrates several shared gene usage biases underpinned by complementary biochemical features evident in a structural comparison. These epitopes are attractive targets for vaccination and other T cell therapies. [Display omitted] •Conserved influenza epitopes are recognized in multiple HLA-DR1+ donors•Shared TRAV-gene usage underpins epitope-specific responses in vitro•Structural analysis identifies biochemical features associated with V-gene selection•CDR3 motifs and enrichments are evident in several shared “public” CDR3 sequences CD4+ T cells orchestrate protection from severe influenza. However, knowledge of epitopes and the molecular patterns associated with recognition across the population is lacking. Greenshields-Watson et al. identify several influenza epitopes from internal proteins and use them to explore the biochemical features that underpin CD4+ T cell responses to influenza.